Transformation of Faculty of Information Management: 1981 to 2015 / Farahusna Ahmad Fadzilah and Nur Syafiqah Shabudin - Ahmad Fadzilah, Farahusna; Shabudin, Nur Syafiqah (Faculty of Information Management, 2015)
The transformation or history of Faculty of Information Management, University Technology MARA (UiTM), is started in 1968 that was earlier known as a School of Library Science. This showed that our faculty was produced more graduated student in this field. It is because University Technology MARA has long been involved in continuing education. The mostly our library today are managed by the library science student. In this article, there are the transformation that was produced by the faculty until today.